Formulation and Effectiveness Testing of Moringa Leaf (Moringa Oleifera) Ethanol Extract Lotion as A Skin Moisturizer - Nasution, Isna Gita Amalia; Ginting, Chrismis Novalinda; Chiuman, Linda (Poltekkes Kemenkes Palu, 2024)
This study delves into the formulation of a lotion using different concentrations (0.5%, 2%, and 5%) of Moringa oleifera leaf ethanol extract, aiming to address the constant exposure of the skin to a prooxidant environment. In Indonesia, the rising interest in exploring natural plants for traditional skincare formulations is attributed to their perceived lower side effects compared to chemical substances. Employing an experimental research approach with a pre-test and post-test control group design, the study focuses on observing and controlling the formulation and effectiveness of Moringa oleifera leaf extract lotion in various skin-enhancing aspects.The research findings reveal that the formulated lotions exhibit distinctive aroma, soft texture, ease of spread, and semi-solid or gel consistency without stickiness. Physical homogeneity suggests a well-blended composition, and the pH values (6.32 for 0.5%, 6.30 for 2%, and 6.28 for 5%) fall within the ideal range, ensuring skin compatibility. Spreadability tests show the 5% concentration has the highest spreadability, while adhesive strength analysis indicates all concentrations meet the criteria for good cream adhesive strength.Furthermore, the efficacy of the lotion is assessed for moisturizing, smoothing, pore-shrinking, wrinkle-reducing, and collagen fiber density-increasing properties. Results indicate the 5% concentration is the most effective across these parameters.In conclusion, the ethanol extract lotion formulated from Moringa oleifera leaves holds promise for enhancing skin health, with the 5% concentration demonstrating the highest efficacy. This research contributes valuable insights to the development of natural skincare products with potential applications in dermatology and cosmetology, aligning with the growing interest in sustainable and effective skincare solutions.